Are CSR leaders less prone to engage in impression management? - Lourenço, I.; Oliveira, J.; Branco, M.; Sofia, A. (XVI Congresso Internacional de Contabilidade e Auditoria, 2017)
This study examines the readability of corporate communication in the CEO letters in the corporate social responsibility (CSR) reports presented by the firms included in the S&P 500 Index. These documents were content analyzed through the use of an automated algorithm provided by Readable.IO. Using a frame of analysis based on the social psychology theory of impression management, we studied the impression management tactics used. The main findings suggest that leading CSR companies (those listed in the Dow Jones Sustainability Index) present more readable CSR information in terms of comprehension and extension. These companies disclose CSR information generally in a positive way. However, these disclosure patterns are mediated by the “goal relevance of the impressions” and the “value of desired goals” related to the impression management tactics used.